Secure Communication for Multiparty OSN (International Journal of Engineering and Computer Science, 2013)
In recent years people go for online social networks (OSNs) to share their personal information using popular social networking sites like Facebook, MySpace and Mylife. These OSNs allow user to enforce privacy concerns over shared data with single user only without providing any model and mechanism to enforce privacy concerns over data associated with multiple users. To overcome this we come across an approach [1] to enable the protection of shared data associated with multiple users by proposing a multiparty authorization framework that allows collaborative management of shared data in OSNs. Multiparty Access Control (MPAC) model is also formulated in order to capture the essence of multiparty authorization requirements. In this MPAC model some users collude with one another so as to manipulate the final access control. This MPAC gave raise to three issues (1) There is no fake identity in OSNs.(2) All users tagged are real users appeared in the photo. (3) All controllers of the photo are honest to specify their privacy preferences [1]. To overcome these issues we utilize a collaborative Face Recognition (FR) framework [9].in to OSNs. We also demonstrate a proof-of-concept prototype as part of an application in Facebook.